2019
DOI: 10.2478/acve-2019-0001
|View full text |Cite
|
Sign up to set email alerts
|

Looking for the causes of and solutions to the issue of honey bee colony losses

Abstract: Colony losses, including those induced by the colony collapse disorder, are an urgent problem of contemporary apiculture which has been capturing the attention of both apiculturists and the research community. CCD is characterized by the absence of adult dead bees in the hive in which few workers and a queen remain, the ratio between the brood quantity and the number of workers is heavily disturbed in favor of the former, and more than enough food is present. Robbing behavior and pests usually attacking the we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
67
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(83 citation statements)
references
References 167 publications
(237 reference statements)
3
67
0
Order By: Relevance
“…The first publication on the varroicidal effect of lithium salts revealed that they have high effectiveness with a systemic mode of action, exerting 100% mite mortality and low toxicity to adult bees, in artificial swarms already at a concentration of 25 mM [10,11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first publication on the varroicidal effect of lithium salts revealed that they have high effectiveness with a systemic mode of action, exerting 100% mite mortality and low toxicity to adult bees, in artificial swarms already at a concentration of 25 mM [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…Alongside novel RNAi-based approaches [9], it was observed that lithium salts may offer promising and easy-to-use chemicals for effectively treating Varroa infestation. Furthermore, treatments have been published where 100% mite mortality was found in the brood-free period with minor or no mortality of adult bees, with certain concentrations of lithium-containing chemicals [10,11]. Lithium chloride has been described as a varroicide that acts in a systemic mode of action in a wide range of concentrations [10].…”
Section: Introductionmentioning
confidence: 99%
“…Given the widespread use of chemicals in all human areas of practice, the bees are not safe from exposure to various types of agropesticides [11]. In North America, for instance, hives have been found to be contaminated by 120 pesticides and their metabolites [44], the most common one being coumaphos.…”
Section: Discussionmentioning
confidence: 99%
“…When V. destructor was fi rst noticed, scientists could readily imagine that it would be a real nuisance causing a disaster to beekeeping [3]. Although some traits of the bee mite remained poorly known [4,5], later it has been recognised that besides causing a decline in the bee population in hives, it also serves as a vector to various bee pathogens [6][7][8][9][10][11]. However, recent research pointed to the fact that viruses are not decisive pathogens: it is highly probable that not they themselves, but Varroa mites are those which are of outstanding importance in producing bee pathology, given that they feed on the body fat [2], which is known to have hugely important functions: besides being a source of fat and proteins, it regulates metabolism and plays a pivotal role in the immunology of the honey bee [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the number of managed honey bee colonies has dramatically declined across North America and Europe since 2006 1 . Although there are many potential causes for the observed declines, pathogens/parasites are considered major threats to the health of honey bees [2][3][4] . There are different kinds of honey bee pathogens/parasites, such as viruses, bacteria, fungi, protozoans, and mites 2 .…”
mentioning
confidence: 99%